The role of data aggregation in the process of selecting a sales forecasting method - Szabela-Pasierbińska, Ewa (Rola agregacji danych w procesie wyboru metody prognozowania sprzedaży, 2011)
The paper presents the role of aggregation in the process of sales forecasting. While explaining the term “aggregation” it was noticed that the notion appears in forecasting at the stage of forecast data analysis and at the stage of forecast construction. In the former case aggregation, although it might cause the loss of certain amount of information on the analysed phenomenon, facilitates or even enables selecting a forecasting model indispensable for establishing a forecast for this phenomenon. In the latter case aggregation enables obtaining forecasts for longer periods or larger areas than the initially established forecasts. The theoretical discussion was illustrated with an empirical example related to forecasting sales of household goods and appliances.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 196, s. 69-82
Keywords: prognozowanie; prognozowanie sprzedaży; forecasting; sales forecasting